LabMELD-based organ allocation increases total costs of liver transplantation: a single-center experience - Bruns, Helge; Hillebrand, Norbert; Schneider, Tobias; Hinz, Ulf; Fischer, Lars; Schmidt, Jan; Goldschmidt, Andreas J. W.; Schemmer, Peter (Clinical transplantation, 2011)
Introduction: In 2006, model for end-stage liver disease (MELD)-based allocation was implemented in the Eurotransplant (ET) region. Sick patients, who in general require more resources, are prioritized. In this analysis, the effect of MELD on costs for liver transplantation (LTx) was assessed. Methods: Total costs for LTx before and after implementation of MELDwere identified in 256 patients from January 2005-December 2007. Forty-nine patients (Re-LTx, HU listings, and 30-d mortality) were excluded from further analysis. The costs of LTx in 207 patients have been correlated with their corresponding labMELD; 84 and 123 LTx before and after implementation of MELD were compared, and patient survival was monitored. Results: A positive correlation exists between labMELD and costs (r2= 0.28; p < 0.05). Only nominal correlation existed between the Child-Pugh classification and costs. The labMELD scores can be stratified into four groups (I: 6–10, II: 11–18, III: 19–24, and IV: >24), with an increase of €15.672 ± 2.233 between each group (p < 0.05). Recipients ÕlabMELD at the time of LTx increased significantly in the MELD-based allocation system. Costs increased by €11.650/patient (p < 0.05), while median survival decreased from 1219 to 869 d (p < 0.05). Conclusion: LabMELD-based allocation increased total costs of LTx. In accordance with other studies, the sickest patients need the most resources.